2015
DOI: 10.1111/1460-6984.12173
|View full text |Cite
|
Sign up to set email alerts
|

The participants’ perspective: how biographic-narrative intervention influences identity negotiation and quality of life in aphasia

Abstract: Our quantitative and qualitative results demonstrated the benefits associated with the biographic-narrative intervention. The participants' sense of self changed through the approach. The findings provide foundations for future work using biographic narrative interventions to influence QoL and identity renegotiation in people with aphasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 30 publications
0
70
0
3
Order By: Relevance
“…Other therapies such as biographic‐narrative therapy (Corsten et al . ), solution‐focused brief therapy (Northcott et al . ) and modified motivation interviewing (Holland et al .…”
Section: Introductionmentioning
confidence: 99%
“…Other therapies such as biographic‐narrative therapy (Corsten et al . ), solution‐focused brief therapy (Northcott et al . ) and modified motivation interviewing (Holland et al .…”
Section: Introductionmentioning
confidence: 99%
“…It also provided a sense of pride and purpose because of the activities that become possible and the roles that can be accessed. Other similar studies [41,42] considering the journey of people with stroke have recognized social identity as a key factor in enhancing quality of life. Past research [13,41] has found themes related to reclaiming social identity included: agency, control, disease concept and doing things as factors which positively impacted on mental health.…”
Section: Discussionmentioning
confidence: 95%
“…Competence in producing personal narratives is considered important for a speaker’s social and psychological well-being as it gives them the opportunity to “make sense” (again) of the experience during the telling [17]. Personal narratives are closely intertwined with cultural identity [3] and are considered “the point at which the individual and culture intersect” [4, p. 323].…”
Section: Introductionmentioning
confidence: 99%
“…Within the World Health Organization’s International Classification of Functioning [19], the ultimate goal of aphasia rehabilitation is to enable PWA to daily participate actively in their natural family environment and community with respect to autonomy, life roles and leisure activities, for example [20]. Activity and participation fosters a healthier quality of life as reflected by research on biographic-narrative intervention [17] and on treatment outcomes important to PWA and their families [20]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation